2017
DOI: 10.1159/000464461
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II/Angiotensin II Receptor Blockade Affects Osteoporosis via the AT1/AT2-Mediated cAMP-Dependent PKA Pathway

Abstract: Animal studies have reported on the benefits of ARB on bone mass. However, the underlying mechanism for angiotensin II (AngII)/AngII receptor blockade (ARB) in regulating bone mass remains elusive. Since high levels of plasma and urine cAMP are observed in osteoporotic and hypertensive patients, we hypothesized that cAMP may be an important molecule for the downstream events of the activation of AT receptors, members of the G-protein-coupled receptor family, in regulating bone turnover. In this study, micro-CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 46 publications
0
19
1
Order By: Relevance
“…In both situations, bone tissue response was modulated by Losartan (Los, 10 −6 M, AT1R blocker), PD123319 (PD, 10 −5 M AT2R blocker), or Losartan + PD123319. Concentrations of AngII, Losartan, and PD123319 used in this study have been previously optimized in bone cell culture studies addressing RAS modulation, being routinely used in the in vitro models [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In both situations, bone tissue response was modulated by Losartan (Los, 10 −6 M, AT1R blocker), PD123319 (PD, 10 −5 M AT2R blocker), or Losartan + PD123319. Concentrations of AngII, Losartan, and PD123319 used in this study have been previously optimized in bone cell culture studies addressing RAS modulation, being routinely used in the in vitro models [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, a recent meta-analysis found that the association of ACEI and ARBs with decreased risk of bone fractures remains inconsistent [ 16 ]. Additionally, RAS modulation with AngII, ACEI, and ARBs (type 1 and type 2 receptors) assessed in experimental disease models of osteoporosis, spontaneous and induced hypertension, diabetes, and knockout models [ 8 , 10 , 17 , 18 , 19 ] showed both positive results [ 20 , 21 ] or no effect [ 22 , 23 ]. Great variability is also reported in cell culture models with diverse degrees of complexity and involving a multiplicity of experimental protocols of RAS stimulation/inhibition, trying to elucidate the subjacent cellular and molecular mechanisms [ 8 , 10 , 12 , 21 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating data have suggested that RAAS might contribute to osteoporosis development and progression. For instance, in vitro studies found that angiotensin Ⅱ could activate osteoclasts, a key mediator in osteoporosis 22,23 . Animal studies using mice or rats showed that renin and angiotensin accelerated BMD decrease and that blockage of them could improve bone quality [22][23][24][25][26][27] .…”
Section: Discussionmentioning
confidence: 99%
“… Wang et al (2018) demonstrated that the RAS components were expressed and up-regulated in synovial tissues of rheumatoid arthritis patients and collagen-induced arthritis rats, and that aberrant activation of RAS in synovial tissues participated in the pathogenesis of rheumatoid arthritis by increasing bone resorption and decreasing bone formation. Zhou et al (2017) found that bone RAS increased bone resorption and decreased bone formation by promoting osteoclast differentiation and repressing osteoblast formation, which eventually resulted in osteopenia in ovariectomized mice. Zhang et al (2014) revealed that activation of local bone RAS could be a significant reason for steroid-induced osteonecrosis in rabbits.…”
Section: Introductionmentioning
confidence: 99%